Perlindungan Hukum Hak-Hak Anak Pengguna Narkoba dan Pertanggungjawaban menurut Hukum Positif di Indonesia - Mila Azizah; M Taofik Makarao; Syarif Fadillah (Jurnal Hukum Jurisdictie, 2020)
Cases of children as drug users are victims of drug abuse who are vulnerable to being part of the drug trafficking circle, even becoming an opportunity for dealers and suppliers to use children as couriers. The main problem of this research is about the legal protection of the rights of children who use drugs and criminal responsibility for children as perpetrators of criminal acts of drug users according to positive law in Indonesia. The research carried out for this thesis is normative legal research with a law and comparative approach. Data collected through primary, secondary and tertiary legal materials which were then analyzed qualitatively to obtain research results regarding the legal protection of the rights of children who use drugs to obtain legal assistance at the stage of investigation, prosecution and court based on the provisions of Law Number 3 of 1997 concerning Juvenile Court and criminal responsibility for children as perpetrators of criminal acts of drug users by undergoing action in the form of rehabilitation as drug abuse based on Law Number 3 of 1997 concerning Juvenile Court.